2016
DOI: 10.1161/strokeaha.116.014531
|View full text |Cite
|
Sign up to set email alerts
|

Cutting the Prehospital On-Scene Time of Stroke Thrombolysis in Helsinki

Abstract: Implementation of the emergency medical services training program successfully decreased the OST of thrombolysis candidates by 10%. Higher expertise level of the ambulance crew was associated with shorter OST, and decisions to consult a physician via telephone were reflected by longer OST.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 8 publications
2
25
0
Order By: Relevance
“…Our finding of a median OST of 21 min is comparable to earlier Finnish and Danish studies, which report OSTs between 18 and 25 min, [7, 18] while an American study has reported OSTs as low as 15 min [12]. Various studies of Mobile Stroke Units (MSUs) have also reported on on-scene time consumption [1921].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our finding of a median OST of 21 min is comparable to earlier Finnish and Danish studies, which report OSTs between 18 and 25 min, [7, 18] while an American study has reported OSTs as low as 15 min [12]. Various studies of Mobile Stroke Units (MSUs) have also reported on on-scene time consumption [1921].…”
Section: Discussionsupporting
confidence: 84%
“…Establishing the first IV access during transport was shown to reduce OST by almost 20% and demonstrates and important opportunity of time reduction. It could be argued that cannulation during transport is more difficult and may also pose a risk to both patient and ambulance personnel [18]. Nonetheless, balancing potential risks and rewards, it should at least be considered to establish IV accesses during transport if possible in order to reduce OST and alarm-to-treatment time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intravenous tissue plasminogen activator (IV tPA) needs to be administered within 4.5 hrs of the last known well time, and earlier treatmentis associated with improved patient outcomes 28. Early recognition, accurate emergency medical services (EMS) dispatch, rapid EMS transport,9 and stroke team activation have helped shorten door-to-IV tPA time, but EMS prenotification of stroke still remains crucial in saving time to treat a stroke patient. EMS prenotification allows the emergency department (ED) and hospital staff to prepare for the patient’s arrival so that appropriate care can be initiated promptly.…”
Section: Introductionmentioning
confidence: 99%
“…A Swedish randomised trial showed that IV thrombolysis rates and hospital treatment delays significantly improved after paramedics were provided with training and the emergency status of stroke ambulance dispatch was raised [13]. An observational study in Helsinki collecting data before and after a simple training package for ambulance personnel showed that on-scene time reduced by an average of 2.5 min, but there was insufficient power to assess the impact on IV thrombolysis treatment rates [14]. An alternative model of ‘mobile stroke units’ (adapted ambulances with computerised tomography (CT) scanner and neurologist on board or video link to a stroke specialist) has been shown to reduce service-level call to needle times (CTNTs) by 15 min in dense urban areas, but the impact on outcomes must be balanced against the additional costs and technical challenges [1517].…”
Section: Introductionmentioning
confidence: 99%